Zinc oxide nanocatalyst mediates cadmium and lead toxicity tolerance mechanism by differential regulation of photosynthetic machinery and antioxidant enzymes level in cotton seedlings. (2021) - N., Priyanka; N., Geetha; T., Manish; S.V., Sahi; P., Venkatachalam
Graphical abstract: Highlights: ZnONPs enhanced plant growth and biomass by alleviation of heavy metal toxicity. Increased level photosynthetic pigments, MDA and protein contents recorded in cotton leaves in co-presence of ZnONPs. The activity of antioxidative enzymes was promoted significantly in the presence of ZnONPs under Cd and Pb induced stress. No distinct genomic alterations were recorded in the RAPD banding pattern. Abstract: Cadmium (Cd) and Lead (Pb) heavy metal pollution induced toxicity severely affects the plant growth and yield of various agriculutral crops worldwide. The present study discuss the prime role of phycomolecules coated zinc oxide nanoparticles (ZnONPs) application on development of heavy metal tolerance mechanism in cotton ( Gossypium hirsutum L.) seedlings better than exposed to Cd and Pb treatments alone. Co-exposure of ZnONPs along with heavy metal treatments significantly promoted the shoot, and root growth as well as biomass compared to control, while it was down-regulated in Cd and Pb exposed seedlings. The intervention of ZnONPs had up-regulated the level of chlorophyll a, b and carotenoid contents in leaves grown under Cd and Pb treatments than the untreated control. Similarly, the level of total soluble protein and malondialdehyde (MDA-lipid peroxidation) contents was significantly increased in the co-presence of ZnONPs along with Cd and Pb treatments over their respective control. Accumulation of antioxidant defense enzymes viz., superoxide dismutase (SOD), catalase (CAT), peroxidase (POX) and ascorbate peroxidase (APX) was up-regulated significantly in seedlings upon co-exposure of ZnONPs with Cd and Pb treatments. Random amplified polymorphic DNA (RAPD) fingerprinting analysis exhibited no genomic changes/alterations in seedlings by co-existence of ZnONPs with heavy metals. Overall, the present results indicate that the addition of ZnONPs with Cd and Pb ion exposure protects cotton seedlings by alleviating heavy metal induced phytotoxicity and promoted physiochemical characteristics via differential regulation of photosynthetic machinery as well as antioxidative defense mechanisms in cotton seedlings. Results strongly suggest that phycomolecule coated ZnO nanoparticles could be effectively used as nanofertilizer to cultivate agronomically important crops in heavy metal polluted soil in the future.